Heat Shock Protein 90 regulates encystation in Entamoeba - Singh, Meetali; Sharma, Shalini; Bhattacharya, Alok; Tatu, Utpal (Frontiers in Microbiology, 2015)
Enteric protozoan Entamoeba histolytica is a major cause of debilitating diarrheal infection worldwide with high morbidity and mortality. Even though the clinical burden of this parasite is very high, this infection is categorized as a neglected disease. Parasite is transmitted through feco-oral route and exhibit two distinct stages namely – trophozoites and cysts. Mechanism and regulation of encystation is not clearly understood. Previous studies have established the role of Heat shock protein 90 (Hsp90) in regulating stage transition in various protozoan parasites like Giardia, Plasmodium, Leishmania and Toxoplasma. Our study for the first time reports that Hsp90 plays a crucial role in life cycle of Entamoeba as well. We identify Hsp90 to be a negative regulator of encystation in Entamoeba. We also show that Hsp90 inhibition interferes with the process of phagocytosis in Entamoeba. Overall, we show that Hsp90 plays an important role in virulence and transmission of Entamoeba.